2004
DOI: 10.1038/oby.2004.25
|View full text |Cite
|
Sign up to set email alerts
|

The Pro12Ala Polymorphism of the PPARγ2 Gene Regulates Weight from Birth to Adulthood

Abstract: PIHLAJAMÄ KI, JUSSI, MAUNO VANHALA, PASI VANHALA, AND MARKKU LAAKSO. The Pro12Ala polymorphism of the PPAR␥2 gene regulates weight from birth to adulthood. Obes Res. 2004;12:187-190. Objective: The Pro12Ala polymorphism in exon B of peroxisome proliferator-activated receptor ␥ 2 (PPAR␥2) gene has been related to obesity, insulin resistance, and risk of type 2 diabetes. In this study, the effect of the Pro12Ala polymorphism on long-term changes in weight and body composition was investigated. Research Methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 11 publications
3
34
3
Order By: Relevance
“…It has been previously proposed that PPAR␥-2 gene could be a mediator of geneenvironment interactions (37)(38)(39). The effect of Ala12 allele on BMI and type 2 diabetes has also been shown to be modified by dietary intake, degree of obesity, and physical activity level (Uusitupa et al, Finnish Diabetes Prevention Study, 2001) (40).…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously proposed that PPAR␥-2 gene could be a mediator of geneenvironment interactions (37)(38)(39). The effect of Ala12 allele on BMI and type 2 diabetes has also been shown to be modified by dietary intake, degree of obesity, and physical activity level (Uusitupa et al, Finnish Diabetes Prevention Study, 2001) (40).…”
Section: Discussionmentioning
confidence: 99%
“…Low prevalence of type 2 diabetes (Altshuler et al 2000) and dyslipidemias (Huang et al 2011) has been associated with the Ala12 allele of PPARG. However, other studies suggest that association between the genotype and BMI may depend on obesity (Ek et al 1999), age (Pihlajamaki et al 2004), dietary uptake of monounsaturated fatty acids (Garaulet et al 2011), and dietary ratio of polyunsaturated to saturated fatty acid (P/S ratio) (Luan et al 2001). Interestingly, dietary P/S ratio has also been shown to have an interaction with PPARG genotype on the effect on serum lipids in cross-sectional studies (Alsaleh et al 2011;Bouchard-Mercier et al 2011), and also in an intervention trial in which saturated fatty acid was replaced by monounsaturated fatty acid (AlSaleh et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently investigated of these is the proline to alanine substitution at codon 12, an amino acid change which reduces receptor activity to natural and synthetic ligands (Gearing et al, 1994). Research into variation at the PPARG locus and BMI has largely involved adults, but in a follow up study on weight and body composition, Pro12Ala was shown to regulate weight and body composition from birth through to adulthood (Pihlajamaki et al, 2004). Importantly, the alanine substitution has been associated with reduced BMI and increased insulin sensitivity in children (Buzzetti et al, 2005;Cecil et al, 2005;Dedoussis et al, 2009), indicating that this variant confers some sort of protection from obesity and type 2 diabetes at an early age.…”
Section: Peroxisome Proliferator-activated Receptor Gene -A Candidatementioning
confidence: 99%